Administrative regime of vaccination - Yordanov, Angel (Law Journal of New Bulgarian University, 2022)
The article aims to reveal both the emergence and historical development of vaccination and its regulatory framework. The subject of study is the administrative and legal regime of vaccination in Bulgaria. The author examines cases from the case law concerning the vaccination process.